The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1519-6984.10115
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional content of bat-consumed fruits in a forest fragment in Southern Brazil

Abstract: The State Park Mata dos Godoy has 42 identified bat species, among which 21 are frugivorous and belong to the Phyllostomidae family. Current study investigated the concentrations of carbohydrate, lipid and protein in fruits consumed by Artibeus lituratus, Carollia perspicillata and Sturnira lilium to understand their potential differentiated food preferences. The Sampling effort it was from April/2013 to March/2014. Animals captured in mist nets were identified in the field and maintained in cotton bags for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…1). All the low crude protein values ( A ) come from a single study 12 . For P. aduncum , P. dumosum , and P. lanceolatum , protein values ( A 2 ) are lower than crude protein values.…”
Section: Resultsmentioning
confidence: 99%
“…1). All the low crude protein values ( A ) come from a single study 12 . For P. aduncum , P. dumosum , and P. lanceolatum , protein values ( A 2 ) are lower than crude protein values.…”
Section: Resultsmentioning
confidence: 99%
“…Em nosso estudo encontramos nas fezes de A. lituratus sementes de S. sisymbriifolium F. insipida, C. pachystachya e C. glaziovii (Tabela 1). Recentemente, para a região do Parque Estadual do Godoy, em Londrina, Batista et al (2017) demonstram que a dieta de A. lituratus é rica não apenas em carboidratos, mas também em lipídeos e proteínas. Frutos de todas as plantas registradas no presente estudo demonstraram conter em sua composição elevadas concentrações de carboidratos e lipídios e ainda pequenas concentrações de proteínas (BATISTA et al, 2017).…”
Section: Discussionunclassified
“…Recentemente, para a região do Parque Estadual do Godoy, em Londrina, Batista et al (2017) demonstram que a dieta de A. lituratus é rica não apenas em carboidratos, mas também em lipídeos e proteínas. Frutos de todas as plantas registradas no presente estudo demonstraram conter em sua composição elevadas concentrações de carboidratos e lipídios e ainda pequenas concentrações de proteínas (BATISTA et al, 2017). Sendo assim, para uma espécie de grande porte, como A. lituratus, e que realiza vários incursos a diferentes árvores, o consumo de frutos de determinadas espécies de plantas fornecem energia, principalmente de carboidratos, que suprem as demandas de alta energia gasta durante a atividade de busca de alimento durante o voo (VOIGT et al, 2010;BATISTA et al, 2017).…”
Section: Discussionunclassified
“…Behavioral studies of frugivorous bats provide evidence that these animals require a variety of food plants to meet their nutritional requirements, including fruit, nectar, pollen, leaves and petioles [ 8 , 9 , 11 – 18 ]. Nutritional studies of frugivorous bat species have primarily focused on macronutrient content [ 12 , 13 , 19 21 ] and only a handful of studies reported micronutrient content of food plants consumed by flying-foxes [ 8 , 14 – 16 ] and the short-nosed fruit bat ( Cynopterus sphinx ) [ 17 ], limiting our ability to accurately predict nutrient requirements. Nutrient analysis of native food plants would provide evidence for how flying-foxes met their nutritional requirements historically and how the introduction of alien food plants might impact the nutrition of insular flying-foxes.…”
Section: Introductionmentioning
confidence: 99%